El efecto de China en el comercio internacional de América Latina - Claudio E. Montenegro; Mariana Pereira; Isidro Soloaga (Estudios de Economía, 2011)
– Using a gravity model, this article presents an analysis of aggregate trade flows aimed at identifying China's impact on Latin America's trade. The results obtained indicate that: i) China's growth in the last years implied a growing supply of exports to this market from most countries in the World, including that of Latin American countries; ii) at the aggregate level, there was no indication that Chinese exports to third markets were crowding out LAC exports to those countries; and iii) a positive relationship between imports from China and exports to third markets was only found for the Southern Cone countries.
Keywords: F10; F12; F15; 330; bilateral trade; gravity model; poisson regression; China; Latin America; Internationale Wirtschaftsbeziehungen; Wirtschaftswachstum; Gravitationsmodell; China; Lateinamerika